A Case Study of AOP and OOP Applied to Digital Hardware Design - Mück, Tiago R.; Gernoth, Michael; Schröder-Preikschat, Wolfgang; Fröhlich, Antônio A. (Proceedings of the 2011 Brazilian Symposium on Computing System Engineering (SBESC), 2011)
In this paper we explore a SystemC-based hardware design method which uses aspect-oriented programming concepts. We have designed a synthesizable resource scheduler at register transfer level by using only features available in the SystemC synthesizable subset. The results show that aspectoriented programming applied to digital hardware design provides a better separation of concerns at the cost of a negligible overhead. © 2011 IEEE.
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.applyi
Keywords: Aspect-oriented programing; Digital hardware design; Reconfigurable hardware